Interdisciplinary studies in higher education; Student centered summer schools of YTU - BEST - Vural, S. Mujdem (ELSEVIER SCIENCE BV, 2012)
Today in higher education, students are one of the pioneers of new responsibility shareholders formed by the reflection of globalization. As one of the responsibilities to increase the awareness on education issues and to gain knowledge through experience, students constructed an organization Board of European Students of Technology (BEST). Throughout Europe, BEST supports interdisciplinary studies since 1989. Three summer schools of Yildiz Technical University BEST will be discussed in the sense of interdisciplinary study examples to evaluate the contributions of student centred education on student' s individual and collective learning styles, participatory design techniques and practices. (C) 2012 Published by Elsevier Ltd.
Keywords: interdisciplinary study; observation and freehand drawings; Education & Educational Research